Seventh Grade Students’ Perceptions on the Use of Zoom in English Learning During Covid 19 in Pematangsiantar - Idawati Situmorang; Hamela Sari Sitompul (Jurnal Scientia, 2021)
The Indonesian government's policy of closing all schools as a step in combating the spread of corona virus disease (Covid 19) result in changes in the learning system. It is undeniable that this causes some confusions for both teachers and students because all learnings must be done at home. On the other hand, learning must still be done. And the best way to keep learning even when staying at home is to use technology. One of the technologies used is Zoom Meeting application. This study aims to find out the perception of seventh grade students on the use of Zoom in English learning during Covid 19. This research was conducted at Methodist Junior High School in Pematangsiantar. There were 37 students as the subjects of the study. Qualitative descriptive was a method used in this study by giving questionnaires in the form of google forms to students. The results of this study showed that the use of Zoom in English learning helps both students and teachers in terms of operation and understanding of learning. This can be seen from the number of students’ responses exceed 50% choosing “Agree” and “Agree Strongly” toward the questionnaire’s statements given. Meanwhile, only in questionnaire number 3 in the statement "Zoom saves internet data, so I always follow Zoom in English learning" there were 46% choosing “Agree” and “Agree Strongly”, while the total number of those who chose “Disagree” and “Disagree Strongly” was 54%. This indicates that approximately 50% of students do not always follow zoom in English learning.